Oil rent, entrepreneurial start-ups, and institutional quality: Insights from African oil-rich countries - Folorunsho M. Ajide; Kenny Adedapo Soyemi (Entrepreneurial Business and Economics Review (EBER), 2022)
Objective: The objective of this study was to examine the moderating effect of institutional quality in the relationship between oil rents and entrepreneurial start-ups for oil-rich countries in Africa. Research Design & Methods: The study employed panel regression techniques that included instrumental variable (IV) estimator to analyse the data of 11 oil-rich countries in Africa over a period of 2006-2018. Findings: The following results emerged. (1) Oil rent's impact is positive and significantly affects entrepreneurial start-ups. (2) The interactive coefficients of oil rents and institutional quality have a negative and significant impact on entrepreneurial start-ups. This means the quality of African institution reduces and leaks out entrepreneurial benefits of oil rents in African oil-rich countries. We establish that institutional quality's threshold at which oil rent would accelerate entrepreneurial start-ups is 2.23 on a five-point scale. Implications & Recommendations: This study revealed that the ability of oil rents to consistently promote entrepreneurial development in oil-rich economies depends on the level of institutional conditions. This situation may create a growth trap for African oil-dependent economies because entrepreneurial start-ups depend on the quality of institutional foundations, which may position the growth inclusiveness and government actions on the right paths. In this context, our empirical findings reveal that African governments need to work on the institutional quality of their economies to reduce the institutional curse of oil rents on African entrepreneurial start-ups. Contribution & Value Added: The article advances our understanding on the nexus of entrepreneurship and oil rents. It is the first study conducted on oil-rich countries in Africa. Moreover, the work differs from the literature by examining the threshold level at which African institutional quality would meaningfully enhance positive relationship between oil rents and entrepreneurial start-ups.
Keywords: M13; N97; O43; 330; Africa; institutions; new business entry; oil rents; panel-corrected standard errors